(NsOBRANIE SO^INENIJ W ^ETYREH TOMAH(B; s (NpO\MY I SATIRY (B/ s (N~ASTX (B3s - (NbAJRON(B, (NdVORDV gORDONs ((NmOSKWA(B: s (NpRAWDA(B, s, 1981)
(Nw TRETIJ TOM WO[LI PO\MY(B, (NSATIRY I PROZA(B.s
(NpROZAs
rus
Keywords: (NpO\ZIQ(B, (NPO\MYs; (NsATIRAs -- (NpROZAs